A simple and effective ground‐based tool for sampling tree flowers at height for subsequent nectar extraction. Issue 11 (9th August 2020) - Scaccabarozzi, Daniela; Campbell, Tristan; Dods, Kenneth
Abstract: Sampling nectar from forest canopies is logistically challenging as it requires physical access to the canopy to a height greater than that can be achieved by hand. The most common solutions comprise the use of cherry pickers, cranes or tree climbers. These techniques are generally expensive, logistically complex, and often involve additional safety risks and specialized technicians to use the equipment/machinery. In addition, access is required up to the tree for cherry pickers and cranes, and tree climbers are often unable to reach the outermost branches. Here, we propose a simple approach based on a special, easy to assemble tool, to sample tree flowers for subsequent nectar extraction, to avoid climbing and cumbersome/expensive equipment. Conducting a study on nectar production of Eucalypt trees (Myrtaceae) in southwest Australia, we conceived a practical ground‐based tool formed by an extendible pole with an adapted container at the end for covering the tree inflorescence with organza and plastic (polyethylene) bags. We experimented with the tool on dozens of trees of each of the co‐occurring species Eucalyptus marginata and Corymbia calophylla, successfully completing the following operational manoeuvres: bagging the inflorescence with an organza bag prior to the nectar collection, then bagging the inflorescence and organza bags with plastic bags if necessary, and cutting the bagged inflorescences from the branch for subsequent nectar extraction. We present the instructions for assembling the tool and we detail the sequence for bagging and sampling flowers from canopy trees, including time‐saving tips. This approach allows efficient sampling of tree flowers for subsequent nectar extraction. To effectively handle the tool while covering the inflorescence, the maximum sample collection height is approximately 10 m. Overall, the tool helps to address limitations related to sampling nectar from medium‐height trees such as costs, risks and time factors. Beyond tree flowers, the tool can be used for sampling flowers of epiphytic and climbing plants, and it could also be used to test for autogamy in flowering trees.